Analisis Penggunaan Majas pada Puisi “Diponegoro” Karya Chairil Anwar - Hura, Dernius; Ndraha, Laurensia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Purpose of this research is to find out and analyze what figures of speech are used in the poem entitled